Study protocol for the Multiple Symptoms Study 3: a pragmatic, randomised controlled trial of a clinic for patients with persistent (medically unexplained) physical symptoms. Issue 11 (15th November 2022) - Mooney, Cara; White, David Alexander; Dawson, Jeremy; Deary, Vincent; Fryer, Kate; Greco, Monica; Horspool, Michelle; Neilson, Aileen; Rowlands, Gillian; Sanders, Tom; Thomas, Ruth E; Thomas, Steve; et al.
Abstract : Introduction: Persistent physical symptoms (which cannot be adequately attributed to physical disease) affect around 1 million people (2% of adults) in the UK. They affect patients' quality of life and account for at least one third of referrals from General Practitioners (GPs) to specialists. These referrals give patients little benefit but have a real cost to health services time and diagnostic resources. The symptoms clinic has been designed to help people make sense of persistent physical symptoms (especially if medical tests have been negative) and to reduce the impact of symptoms on daily life. Methods and analysis: This pragmatic, multicentre, randomised controlled trial will assess the clinical and cost-effectiveness of the symptoms clinic intervention plus usual care compared with usual care alone. Patients were identified through GP searches and mail-outs and recruited by the central research team. 354 participants were recruited and individually randomised (1:1). The primary outcome is the self-reported Physical Health Questionnaire-15 at 52 weeks postrandomisation. Secondary outcome measures include the EuroQol 5 dimension 5 level and healthcare resource use. Outcome measures will also be collected at 13 and 26 weeks postrandomisation. A process evaluation will be conducted including consultation content analysis and interviews with participants and key stakeholders. Ethics and dissemination: Ethics approval has been obtained via Greater Manchester Central Research Ethics Committee (Reference 18/NW/0422). The results of the trial will be submitted for publication in peer-reviewed journals, presented at relevant conferences and disseminated to trial participants and patient interest groups. Trial registration number: ISRCTN57050216 .